PENGARUH KONFLIK KERJA, STRES KERJA, DAN BEBAN KERJA TERHADAP TURNOVER INTENTION DIVISI E2 PRODUCTION ENGINEERING DI PT EPSON INDUSTRY - Dendi Wahyudi; Affan Rafi; Pupung Purnama Sari (Bajang Institute, 2024)
This study aims to determine how the effect of work conflict, work stress and workload on Turnover intention in the E2 Production Engineering Division at PT. INDONESIA EPSON INDUSTRY. By using a quantitative method, data from this study were collected from 61 E2 Production Engineering employees. The sampling technique uses a non-probability sampling technique with purposive sampling category. The analytical method used in this study is the data/instrument quantity test, classical assumption test, hypothesis testing and multiple linear regression analysis with the help of SPSS 26 software as a tool for analysis. The results of this study indicate that the work conflict variable has a significance value (0.025) < (0.05), work stress has a significance value (0.298) > (0.05) and workload has a significant value (0.000) > (0.05), so it can be concluded that only one independent variable, namely work conflict, has a positive and significant effect on turnover intention, while the variables work stress and workload have no significant effect. The results of the simultaneous test (F test) have a significance value (28.227) > (0.05) and (t test) obtained ttable (0.2564). a coefficient of determination (R2) of 0.773 or 77.3% of the Turnover intention variable is influenced by work conflict, while the remaining 22.7% is explained by other variables not used in this study